Instilling Confidence in First Aid and CPR Training: Alternatives to Traditional Methods (International Journal of First Aid Education)
The conference weighed the benefits of using simulation manikins able to give performance feedback in CPR and first aid training to the prohibitive cost, particularly of their high feedback models. Participants engaged with different models and discussed the effectiveness of lower feedback manikins for first time trainees versus higher feedback when training in advanced skill sets.